2019
DOI: 10.19184/ams.v5i2.9625
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between The Use of Personal Protective Equipment (PPE) and Soil-Transmitted Helminths Infection in the Workers of Kaliputih Plantation Jember Regency

Abstract: This study aimed to investigate the correlation between the use of Personal Protective Equipment (PPE) and the status of Soil-Transmitted Helminths infection in the workers of Kaliputih plantation in Jember Regency. The research method applied was Analytic observational with a Cross-sectional approach. The population, as well as the sample, were all workers of Kaliputih Plantation, Sumber Bulus Village, Ledokombo District, Jember Regency, by the total of 63 people. The sampling technique was the Total sampling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 3 publications
0
4
0
2
Order By: Relevance
“…STH through the soles between the toes, especially hookworm larvae. Workers who do not wear gloves at risk of STH infection are 8,8 times greater than those who wear gloves (Baidowi, et al, 2019).…”
Section: Resultsmentioning
confidence: 96%
“…STH through the soles between the toes, especially hookworm larvae. Workers who do not wear gloves at risk of STH infection are 8,8 times greater than those who wear gloves (Baidowi, et al, 2019).…”
Section: Resultsmentioning
confidence: 96%
“…A previous study reported that there was a relationship between hand washing and the incidence of helminth infections [28]. Washing hands is an important activity because worm eggs can be ingested through contaminated nails [29]. Washing hands with soap also has a significant influence on the incidence of soil-transmitted helminth infections.…”
Section: Discussionmentioning
confidence: 99%
“…Soil contamination by STH can negatively impact the environment because it can be a source of pollution for water and plants that live around it (Muttaqien, 2018). Research conducted by Baidowi et al (2019) also showed a significant association between PPE use and STH infection status, so it is important to study it. Questions regarding environmental sanitation in this study are also less comprehensive, for example, not asking about waste disposal facilities and wastewater disposal channels (SPAL) (Kusumawardani, 2018).…”
Section: Discussionmentioning
confidence: 99%